Lexical Inventiveness and Creativity in Children’s Literature by Tina Arnuš Pupis (Preučevanje otroške in mladinske književnosti, 2025)
In this paper, we explore the lexical inventiveness and creativity in the children’s literary works by Tina Arnuš Pupis. There are five collections of stories included in the in-depth examination and analysis: Za devetimi drevesi (2017), Božo in Vili (2018), Na gozdni južini (2020), Nad gozdom se nekaj svetlika (2022) and Čivkarije s kmetije (2023). These works reveal several kinds of originality and playfulness at the lexical level, such as word-formation innovation, wordplay based on sound and meaning - paronyms, phraseological renewals, and introduce young readers to the immense diversity, vitality and playful value of the Slovenian language. Thus, they enrich the child’s reading experience, their vocabulary and their own creativity.